2021
DOI: 10.3390/coatings11101236
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Film Forming Law and Characteristics for an Air Static Spray with a Variable Position of the Plane

Abstract: In order to accurately establish the film thickness distribution model of a static spraying plane with air gun displacement, the film forming law and characteristics of the static spraying plane with air gun displacement were analyzed. The spray simulation model was established by the Euler–Euler method, and the spray process and film forming condition were calculated. The numerical simulation results show that oblique spraying has a large influence on the near-surface liquid velocity. With the increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The microscopic mechanism of spray film thickness build-up was investigated, 5 and the distribution pattern of film thickness and the causes of film formation were explained at the microscopic level by combining a multi-field coupled flow field theory model with a film thickness distribution model. Zeng et al 6 and Liu 7 conducted a series of spraying experiments with a spray gun under tilted conditions and established a coating thickness distribution model based on the Gaussian sum model with variable tilt angle. The experiments showed that the Gaussian sum model 8 also has high fitting accuracy in describing the coating growth rate for spraying at different inclination angles.…”
Section: Introductionmentioning
confidence: 99%
“…The microscopic mechanism of spray film thickness build-up was investigated, 5 and the distribution pattern of film thickness and the causes of film formation were explained at the microscopic level by combining a multi-field coupled flow field theory model with a film thickness distribution model. Zeng et al 6 and Liu 7 conducted a series of spraying experiments with a spray gun under tilted conditions and established a coating thickness distribution model based on the Gaussian sum model with variable tilt angle. The experiments showed that the Gaussian sum model 8 also has high fitting accuracy in describing the coating growth rate for spraying at different inclination angles.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [16][17][18][19][20] studied the influence of different spraying parameters on film thickness uniformity. Liu et al [21] employed simulation methods to study the flow of gas and coarse powder in the electrostatic process. Chen et al [9] focused on the plane spray process and identified the significant impact of spraying height and angle on film thickness uniformity.…”
Section: Introductionmentioning
confidence: 99%